2020
DOI: 10.26434/chemrxiv.13200281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Inhibitors of the Main Protease of SARS-CoV-2 Identified via a Molecular Dynamics Simulation-Guided in Vitro Assay

Abstract: <div>For the COVID-19 pandemic caused by SARS-CoV-2, there are currently no effective drugs or vaccines to treat this coronavirus infection. In this study, we focus on the main protease enzyme of SARS-CoV-2, 3CL pro , which is critical for viral replication. We employ explicit solvent molecular dynamics simulations of about 150 compounds docked into 3CL pro ’s binding site and that had emerged as good main protease ligands from our previous in silico screening of over 1.2 million compounds. By incoporati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A recent CADD-directed fluorogenic enzyme inhibition assay reported corilagin and rhoifolin, two natural products of African origin, with micromolar range inhibitory activity against the main protease (3CLpro) enzyme of the SARS-CoV2 ( Loschwitz et al, 2020 ). Interestingly, the investigation which had commenced with the screening of an over 1.2 million virtual compound library ( Olubiyi et al, 2020 ) identified corilagin and rhoifolin in the top eight compounds with respect to main protease inhibitory activity.…”
Section: Methodsmentioning
confidence: 99%
“…A recent CADD-directed fluorogenic enzyme inhibition assay reported corilagin and rhoifolin, two natural products of African origin, with micromolar range inhibitory activity against the main protease (3CLpro) enzyme of the SARS-CoV2 ( Loschwitz et al, 2020 ). Interestingly, the investigation which had commenced with the screening of an over 1.2 million virtual compound library ( Olubiyi et al, 2020 ) identified corilagin and rhoifolin in the top eight compounds with respect to main protease inhibitory activity.…”
Section: Methodsmentioning
confidence: 99%
“…To test the reliability of the resulting force field parameters, we applied them in energy minimizations of the 160 molecules using their structures as obtained from docking to 3CL pro [15] , which were also used for the force field parameterization as starting structures. These calculations were realized with GROMACS 2018 [16] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Afterwards, we applied the newly derived force field parameters in 20 ns MD simulations of the molecules docked to 3CL pro using GROMACS 2018 and AMBER14SB [18] as force field for the protein. For 99 of the ligands that fulfilled specific structural requirements for inhibitor design reported in [15] , the MD simulations were extended to 100 ns. All MD simulations (whether 20 ns or 100 ns) finished successfully without any stability or incompatibility issues arising.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%